meningkatkan minat entrepreneurship dan pemahaman konsep siswa melalui model PBL-Networked berbasis etnosains - Mela Agustia; M. Dwi Wiwik Ernawati; Pinta Murni (Jurnal Penelitian Pendidikan IPA, 2023)
This study aim to determine the effect of the implementation of the ethnoscience-based PBL-Networked model on students' understanding of the concept and interest in entrepreneurship. The research was conducted using a quasi-experimental approach with nonequivalent control group design. The research subjects were class VII students of SMPN 4 Sungai penuh. Determination of the sample used purposive sampling technique. The data were obtained from the results of the pretest and posttest as well as the student interest in entrepreneurship questionnaire. The instrument is used after being validated by a team of experts. Based on data analysis, that the implementation of the ethnoscience-based Problem Based Learning learning model has an influence on students' understanding of concepts and interest in entrepreneurship. Ethnoscience-based PBL-Networked model learning tools are effective in significantly increasing students' understanding of concepts and interest in entrepreneurship. The effect on students' understanding of concepts and interest in entrepreneurship is higher in the implementation of the ethnoscience-based PBL-Networked model than in conventional classes. This is based on the results of the One way MANOVA test showing a significance value of 0.000 which is less than the significance level Î±= 0.005, so it can be concluded that there is an average difference in increasing understanding of concepts and students' interest in entrepreneurship that is significant between students who learn using the ethnoscience-based PBL-Networked learning model and students who use learning tools that are already available on the Merdeka Belajar Platform